Nonlinear Interactions of Exchange Rate and Stock Market in Iran - Abbasifard, Mohammad; Sabet, Seyed Abdol Hamid; Salehi Rezveh, Masoud; Hosseinpoor, Abdolkarim (Business, Marketing, and Finance Open, 2024)
A group of economists believes that with the increase and severe fluctuations in the exchange rate, the stock market, due to the rising stock prices, serves as a suitable haven for individuals' assets. However, others argue that with the sharp increase in the exchange rate and the associated risk, individuals lose interest in investing in the stock market. This study examines the effects of the exchange rate on the stock market and the changes in stock market prices on the exchange rate during the period from 1983 to 2021 using the nonlinear Markov-switching method. The results indicate that the effect of the exchange rate on stock market prices is significant, and the means in the first and second regimes of the model are also significant. For a one percent increase in the exchange rate, the stock market price index increases by 0.65 percent. This hypothesis is confirmed and aligns with flow-oriented models. Flow-oriented models assume that a country's current account and balance of payments are two important determinants of the exchange rate. Accordingly, changes in the exchange rate affect international competitiveness and the trade balance, thereby impacting real economic variables such as production and income, as well as the future and current cash flows of companies and their stock prices. The results show a positive effect of stock prices on the exchange rate, which is statistically and theoretically significant. For a one percent increase in stock prices, the exchange rate decreases by 0.21 percent, which is also statistically and theoretically significant.